The Order of Cancer: A Theory of Malignant Progression by Inverse Morphogenesis - Höckel, Michael; Behn, Ulrich (Frontiers in Oncology, 2019)
Local spread patterns of malignant tumors follow permissive tissue territories, i.e. cancer fields, as shown for cervical and vulvar carcinoma. The cancer fields are associated in reverse order to the mature derivatives of the morphogenetic fields instrumental in the stepwise development of the tissue from which the tumor arose. This suggests that cancer progression may be linked to morphogenesis by inversion of the cellular bauplan sequence. Successive attractor transitions caused by proliferation-associated constraints of topobiological information processing are proposed for both morphogenesis and cancer. In morphogenesis these transitions sequentially activate bauplans with increasing complexity at decreasing plasticity restricting the permissive territories of the progenitor cell populations. Somatic mutations causing proliferation in domains normally reserved for differentiation trigger the inverse cascade of bauplan changes that increase topobiological plasticity at decreased complexity and stepwise enlarge the permissive territory of neoplastic cells consistent with the clinical manifestations of cancer. The order provided by the sequence of attractor transitions and the defined topography of the permissive territories can be exploited for more accurate tumor staging and for locoregional tumor treatment with higher curative potential.